Complement activation and M2-like macrophage accumulation in anti-MDA5 monoclonal antibody–induced hepatic injury in mice - Koga, Takuma; Zaizen, Yoshiaki; Suzuki, Hiroyuki; Sugi, Suzuna; Hozumi, Hironao; Sakamoto, Noriho; Suda, Takafumi; Mukae, Hiroshi; Kusano, Hironori; Kawahara, Akihiko; Akiba, Jun; Kawaguchi, Takumi; et al. (Frontiers in Immunology, 2026)
BackgroundPatients with anti–melanoma differentiation–associated gene 5 (MDA5) antibody–positive dermatomyositis (DM) frequently develop rapidly progressive interstitial lung disease and may also exhibit hepatic dysfunction, yet the mechanisms of hepatic injury remain poorly defined. We investigated the roles of M2−like macrophages and complement activation in hepatic injury associated with anti−MDA5 antibody–positive DM.MethodsLiver specimens from five autopsy cases of anti-MDA5 antibody–positive DM were examined for the presence of CD80-positive M1-like and CD206-positive M2-like macrophages. To establish a model of antibody-mediated hepatic injury, human MDA5 transgenic mice were treated with in-house anti-human MDA5 monoclonal antibodies. The contribution of complement was assessed by comparing hepatic pathology between wild-type and complement component C3-deficient MDA5 transgenic mice. Liver tissues were analyzed by immunohistochemistry and western blotting, and single-cell RNA sequencing libraries were generated from snap-frozen mouse liver samples.ResultsAutopsy liver specimens demonstrated the presence of CD80-positive M1-like and CD206-positive M2-like macrophages. In human MDA5 transgenic mice, administration of anti−human MDA5 monoclonal antibodies induced hepatic injury accompanied by increased infiltration of CD206-positive M2-like macrophages. This hepatic injury was markedly attenuated in C3-deficient MDA5 transgenic mice, supporting an important role for complement activation in this model.ConclusionComplement activation and the accumulation of M2-like macrophages are associated with anti-human MDA5 monoclonal antibody–induced hepatic injury in mice. These findings provide mechanistic insight into antibody–complement–macrophage interactions and suggest that modulation of complement pathways may represent a potential therapeutic approach to limit liver and systemic involvement in this disorder.